Utilization of Household Waste into Eco-Enzyme in Gitik Village, Rogojampi District, Banyuwangi - Ari Istanti; Sari Wiji Utami (LP2M Universitas Jember, 2022)
The waste heap of Banyuwangi Regency in 2019 was ± 3,387 m3/day with an increasing trend over the last 10 years. It came from settlements, markets, parks, drainage, and other places, which only part of it could be transported to the landfill due to the declining capacity of the landfill. In addition, waste management services mostly only cover urban areas, while in rural areas are usually carried out on-site by people as did in Gitik Village, Rogojampi District. Waste management did traditionally and partly subscribing to waste transport services. Waste transported by the service is only dumped with an open dumping way, due to the unavailability of landfil facilities in Gitik Village. The existence of waste transport services has not been utilized by all the rural people, because some of them were constrained by the cost of waste service fees. As a result, many piles of household waste are still found in various places that cause environmental pollution. The most common complaint felt by the people regarding the impact of pollution is the pungent smell of waste which usually comes from household organic waste. The solution that can be done to overcome these problems is to process household organic waste into eco-enzymes. The eco-enzyme produced from this program can be used by people for many household activities including farming. In addition, environmental cleanliness can also be improved by reducing the amount of household organic waste that is disposed of around settlements.